Aerobic fitness is associated with greater hippocampal cerebral blood flow in children. (August 2016) - Chaddock-Heyman, Laura; Erickson, Kirk I.; Chappell, Michael A.; Johnson, Curtis L.; Kienzler, Caitlin; Knecht, Anya; Drollette, Eric S.; Raine, Lauren B.; Scudder, Mark R.; Kao, Shih-Chun; Hillman, Charles H.; Kramer, Arthur F.
Abstract: The present study is the first to investigate whether cerebral blood flow in the hippocampus relates to aerobic fitness in children. In particular, we used arterial spin labeling (ASL) perfusion MRI to provide a quantitative measure of blood flow in the hippocampus in 73 7- to 9-year-old preadolescent children. Indeed, aerobic fitness was found to relate to greater perfusion in the hippocampus, independent of age, sex, and hippocampal volume. Such results suggest improved microcirculation and cerebral vasculature in preadolescent children with higher levels of aerobic fitness. Further, aerobic fitness may influence how the brain regulates its metabolic demands via blood flow in a region of the brain important for learning and memory. To add specificity to the relationship of fitness to the hippocampus, we demonstrate no significant association between aerobic fitness and cerebral blood flow in the brainstem. Our results reinforce the importance of aerobic fitness during a critical period of child development.